EVALUATION OF ORGANOLEPTIC PUDDING MORINGA LEAF (Moringa oleifera) BASED ON VARIATIONS ADD SUGAR - Silahoy, Frisca; Smith, Alwi; Liline, Sintje (RUMPHIUS, 2021)
Moringa plant is a multipurpose plant that contains many important nutrients needed by the body such as calcium, vitamin B, vitamin A, vitamin C, protein and potassium. Based on this nutritional content, Moringa plants can be processed into vegetable products, namely buding products that are useful and nutritious. To gain acceptance regarding the preferences of consumers or the public in liking a food or beverage product, it is necessary to carry out an organoleptic test. The aim of this research was to determine the organoleptic quality of pudding products made from Moringa oleifera leaves based on variations in the addition of 100gr, 150gr and 200gr sugar. The method used is descriptive research to analyze the level of liking for pudding products. The research results showed that the organoleptic tests on pudding products made from Moringa oleifera leaves were different based on variations in the addition of 100g, 150g and 200g sugar. The variation in adding 100g of sugar shows the organoleptic results of the pudding product with a rather attractive color, slightly sweet taste, soft texture and a somewhat distinctive Moringa aroma. The variation in adding 150g of sugar shows the organoleptic results of the pudding product with a rather attractive color, sweet taste, soft texture and a somewhat distinctive Moringa aroma. The variation in adding 200g of sugar shows the organoleptic results of the pudding product with a rather attractive color, sweet taste, soft texture and a distinctive Moringa aroma.